China's Integration Into the World Economy : Implications for Developing Countries - Yang, Yongzheng (IMF Working Papers; Working Paper ;, 2003)
Although the rest of the world had waited a long time for China to open up, feelings were mixed when it actually did and began to integrate rapidly with the world economy. With the country's recent accession to the World Trade Organization (WTO), many of its trading partners are increasingly concerned that China's competition in the world goods and capital markets may adversely affect their own growth prospects. This paper examines the implications of China's WTO accession for other developing countries in the context of the country's long-term process of growth and opening up. The paper argues that China's integration into the world economy will inevitably impose adjustment costs on its trading partners in the short-to-medium term, but the benefits it generates are likely to dominate in the long run.